Alternative Remittance Systems and Terrorism Financing : Issues in Risk Management - Vaccani, Matteo (World Bank, 2012)
Terrorism can endanger innocent human life and tear the very threads that hold society together, namely, trust and security. Governments have mobilized a variety of tools in response, ranging from the political to the economic. In attempting to prevent and detect terrorist financing and other forms of material support, those offering financial services have been required to heighten their vigilance of potential terrorist abuse of those services. While protecting financial services from potential abuse, care should be taken not to deny access to those services to those most in need. Dejection and social exclusion are very often conducive to terrorism; therefore, ensuring inclusion of the disenfranchised and creating possibilities for their advancement are key parts of the broader, long-term struggle against terrorism and extremism. The paper begins with a brief description of alternative remittance system (ARS) models and their prevalence. It then covers their potential relationship with terrorist financing, citing cases where ARS have been abused for terrorism financing (TF) purposes. Ways in which countries may control these risks and indications of their effectiveness are covered next. The final chapter provides recommendations on how best to mitigate the risks while ensuring legitimate access to financial services via ARS.